PERFORMANCE COMPARISON OF ISLAMIC PORTFOLIOS WITH AFRICAN INDEX - Balde, Moustapha; Konte, Mamadou A.; Sene, Babacar (International Journal of Islamic Banking and Finance Research, 2021)
The objective of this study is to see if the "sharia compatible" stock portfolios common to the various stock exchanges have better returns than the classic African indices. We propose two new methodologies based on the median statistic to build sharia-compliant portfolios to which we add the Dow Jones Islamic Market World (DJIMI) methodology. These three Islamic portfolios are compared with 13 African stock market indices (JTOPI, DCIBT, BRVM10, BRVMCI, MDEX, NSE20, MASI, NGSE30, FTN098, ALSIUG, DSEI, TUNINDEX, LASILZ). First, we looked at the returns and volatilities of weekly and monthly data for Islamic portfolios and classic indices and compared the spreads of their returns and risks. We find the results to be quite divergent, although we can see a trend that Islamic portfolios are more profitable and riskier than conventional indices; for both weekly and monthly data. We show with risk-adjusted performance analysis that Islamic portfolios outperform traditional index. JEL Classification Codes: G10, G11, G12, G14, G53.